0.5-V 16 nW Low-Pass Filter for Bio-Signal Applications - Punnavich Phatsornsiri; Montree Kumngern; Fabian Khateb; Tomasz Kulej; Natapong Wongprommoon; Usa Torteanchai (My University, 2024)
This study presents a low-voltage, ultra-low power fully-differential low-pass filter for bio-signal applications using multiple-input fully differential operational transconductance amplifiers (MIFD OTA). This work shows that a low-pass filter using multiple-input OTA can reduce the number of OTAs and power consumption. The low-pass filter can be applied to biomedical signal processing applications. The low-pass filter was simulated using the 0.18 μm (CMOS) technology from TSMC with a supply voltage of 0.5 V. The simulation result shows that the filter has a static power consumption of 16 nW and a 140-Hz bandwidth when operating from a supply voltage of 0.5 V. Input frequency of 10 Hz with an amplitude of 220 mV, the new proposed filter provides a dynamic range of 72.2 dB, total harmonic distortion of 1 %.
Keywords: Analog and Mixed-Signal Circuit Design; Neuroscience and Neural Engineering